Pemanfaatan Media Sosial Instagram Sebagai Strategi Pemasaran Kerupuk Melarat di Desa Setu Kulon, Kec Weru, Kab Cirebon - Liskawati Liskawati; Cantika Aura; Muzayyinah Muzayyinah; William Chandra Winata; Kiki Amelia; Shello Raphael Emanuel; Reza Pramudiansyah; Boymart L Nadapdap; Aji Sutiyoso; Elisabet Roswinda Siringo Ringo; Ade Elza Surachman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This Community Service Program (PKM) aims to improve the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) of poor crackers in Setu Kulon Village, Weru District, Cirebon Regency, through Instagram-based digital promotion strategies. The problems faced by partners include minimal digital literacy, limited promotion, and still relying on conventional marketing. Through training activities, mentoring, and promotional content creation, students play an active role as digital transformation facilitators for business actors. The results of the activities show an increase in the ability of partners to manage social media accounts and the opening of new markets outside the region. This activity proves that the use of social media can be an effective, cheap, and applicable solution in the development of local-based traditional MSMEs